Pola Pengobatan Infeksi Saluran Pernafasan Akut (Ispa) Pediatrik Rawat Inap Di Rsud Dr. Soediran Mangun Sumarso Wonogiri - Pramita, Biska Kusuma Dewi; Endrawati, Susi; Wahyuningsih - Politeknik Kesehatan Bhakti Mulia, Sri Saptuti (IJMS - Indonesian Journal on Medical Science, 2019)
Abstract: Acute Respiratory Infection (ISPA) is an infection that occurs in the upper respiratory tract and lower respiratory tract. Infection infection is also a lot of attacks all ages, but infants and toddlers are most vulnerable to infected with this disease.This study aims to see the pattern of treatment pattern in the case of ARD of pediatric patient inpatient in dr. Soediran Mangun Sumarso Wonogiri October-December 2016, and to know the allegiance of management according to World Health Organization (WHO): Model Formulary for children 2010 and the Ministry of Health of the republic Indonesia: Pharmaceutical Care for Respiratory Infections Disease 2005. This research used Non Experimental research. Data were taken with descriptive approach and retrospective data collection.This study showed that 24 patients with pediatric ARD, among them female patients 54.16% and the remaining men 45.83%. Acute Respiratory Infection (ARI) therapy is done with basic therapy (antibiotics) and supportive therapy (symptomatic). The results of the study show 1). The pattern of treatment of ARI in pediatric patients hospitalized in RSUD dr. Soediran Mangun Sumarso Wonogiri is in accordance with the management guidelines of the World Health Organization (WHO): Formulary for children 2010 and Republic of Indonesia Ministry of Health: Pharmaceutical Care for Respiratory Tract Infections 2005, 2). Treatment of pediatric ARI uses an average of 100% antibiotic therapy. The most widely used supportive therapy drugs are gastrointestinal drugs with a percentage of 88%, 63% analgesic-antipyretic drugs, 62% use of respiratory tract medicine and 17% use of antihistamine drugs.Keywords: Acute Respiratory Infections (ARI), pediatrics, treatment, infections. Abstrak: Infeksi Saluran Pernafasan Akut (ISPA) merupakan infeksi yang terdapa tpada saluran pernafasan atas maupun saluran pernafasan bawah. Infeksi infeksi ini juga banyak menyerang semua umur, tetapi bayi dan balita yang paling rentan untuk terinfeksi penyakit ini. Penelitian ini bertujuan untuk melihat gambaran Pola pengobatan kasus ISPA pasien pediatrik rawat inap di RSUD dr. Soediran Mangun Sumarso Wonogiri Oktober-Desember 2016, dan untuk mengetahui kesesuaiaan penatalaksanaan menurut World Health Organization (WHO): Model Formulary for children 2010 dan Depkes RI: Pharmaceutical Care untuk penyakit Infeksi Saluran Pernafasan 2005. Penelitian ini menggunakan penelitian Non Eksperimental. Data diambil dengan dari analisa data pendekatan deskriptif dan pengumpulan data retrospektif. Penelitian dari 24 pasien ISPA pediatrik, terdapat pasien perempuan 54,16 % dan laki-laki 45,83 %. Terapi Infeksi Saluran Pernafasan Atas (ISPA) dilakukan dengan terapi pokok (antibiotik) dan terapi suportif (simptomatik). Hasil penelitian menunjukkan 1). Pola pengobatan ISPA pasien pediatrik rawat inap di RSUD dr. Soediran Mangun Sumarso Wonogiri sudah sesuai dengan pedoman penatalaksanaan dari World Health Organization (WHO): Model Formulary for children 2010 dan Depkes RI: Pharmaceutical Care untuk penyakit Infeksi Saluran Pernafasan 2005, 2). Pengobatan ISPA pediatrik rata- rata menggunakan terapi obat antibiotik sebanyak 100%. Obat - obat terapi suportif yang paling banyak digunakan adalah obat saluran cerna dengan prosentase 88%, obat analgetik-antipiretik 63%, penggunaan obat terapi saluran nafas 62% dan penggunaan obat antihistamin 17%.Kata kunci: Infeksi Saluran Pernafasan Akut (ISPA), pediatrik, pengobatan, infeksi.